Analisis SWOT dalam Menentukan Strategi Pemasaran (Studi Kasus Mie Gacoan Antasari Bandar Lampung) - Kulsum, Umi; Tanti, Tanti; Arroisah, Ulfia Anis; Sanjaya, Vicky F (Lembaga Publikasi Ilmiah Nusantara, 2024)
This study analyzes the marketing strategy of Mie Gacoan using the SWOT (Strengths, Weaknesses, Opportunities, Threats) method to formulate relevant competitive strategies. Through the IFE (Internal Factor Evaluation) matrix, strengths such as unique menu variations, competitive pricing, and strategic locations were identified. Meanwhile, weaknesses include limited production capacity and dependency on local raw materials. The EFE (External Factor Evaluation) matrix highlights major opportunities, including the fast-food consumption trend and the growth of digital platforms, as well as threats such as intense competition and raw material price fluctuations. The analysis results indicate that Mie Gacoan is positioned in Quadrant I, suggesting the potential to adopt an aggressive growth strategy. This strategy includes menu innovation, market expansion through digital platforms, and increasing production capacity. With a total IFE score of 3.80 and EFE score of 4.20, Mie Gacoan has significant opportunities to enhance its competitiveness in the fast-food market.